Neural Engineering - He, Bin (Bioelectric Engineering, 2005)
About the Series: Bioelectric Engineering presents state-of-the-art discussions on modern biomedical engineering with respect to applications of electrical engineering and information technology in biomedicine. This focus affirms Springer's commitment to publishing important reviews of the broadest interest to biomedical engineers, bioengineers, and their colleagues in affiliated disciplines. Recent volumes have covered modeling and imaging of bioelectric activity, neural engineering, biosignal processing, bionanotechnology, among other topics. Key Features of this Volume: Neural Engineering, Bioelectric Engineering Volume 2, contains reviews and discussions of contemporary and relevant topics by leading investigators in the field. It is intended to serve as a textbook at the graduate and advanced undergraduate level in a bioengineering curriculum. The topics include: - Neural Prostheses - Neural Interfacing - Neural Robotics - Functional Neural Stimulation - Neural Imaging - Neural Computation - Neural Networks - Neural System Identification and Prediction - Retinal Neuroengineering This principles and applications approach to neural engineering is essential reading for all academics, biomedical engineers, neuroscientists, neurophysiologists, and industry professionals wishing to take advantage of the latest and greatest in this emerging field. About the Editor: Bin He, PhD., IEEE Fellow, is a leading figure in the field of bioelectric engineering. An internationally recognized scientist with numerous publications, Dr. He has served as the President of the International Society of Bioelectromagnetism and as an Associate or Guest Editor for nine international journals in the field of biomedical engineering. Dr. He is currently Professor of Biomedical Engineering at the University of Minnesota.